Use the arithmetic mean-geometric mean inequality to establish the following results:

(a) If $nt > -1 $, then $(1-t)^{n} \geq 1 - nt$

(b) If $-x < n < m$, then $(1+x/n)^{n} \leq (1 + x/m)^{m}$


(a) I had no success at trying to prove it using the AM-GM inequality. Thus I've tried to apply induction.

The base case is true, since for $n = 1$ we get that $(1-t)^{1} = 1 - t = 1 - 1\cdot t$.

Now let us assume that it holds for some natural number $n\geq 1$ and we shall prove it holds for $n + 1$ too.

Indeed, one has that \begin{align*} (1-t)^{n+1} = (1-t)^{n}(1-t) \geq (1-nt)(1-t) = 1 - (n+1)t + nt^{2} \geq 1 - (n+1)t \end{align*} and we are done.

(b) Similarly, we shall prove it applying induction on $m$. For $m = 2$ it is true, because \begin{align*} n < 2 \Rightarrow n = 1 \Rightarrow \left(1 + \frac{x}{2}\right)^{2} = 1 + x + \frac{x^{2}}{4} \geq 1 + x \end{align*}

But then I get stuck.

Could someone please finish the induction proof and provide a solution based on AM-GM inequality?

Any contribution is appreciated.

  • $\begingroup$ You can not use induction here or you need to say that $m$ and $n$ are natural numbers. $\endgroup$ – Michael Rozenberg Jul 8 '20 at 1:27

We need also $n>0$, otherwise your inequality is wrong.

For $n>0$ since $$\frac{n}{m}+\frac{m-n}{m}=1,$$ By AM-GM we obtain $$1+\frac{x}{m}=\frac{n}{m}\left(1+\frac{x}{n}\right)+\frac{m-n}{m}\geq\left(1+\frac{x}{n}\right)^{\frac{n}{m}}\cdot1^{\frac{m-n}{m}}=\left(1+\frac{x}{n}\right)^{\frac{n}{m}},$$ which gives your inequality.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.